Abnormal real operations, real earnings management, and subsequent crashes in stock prices - Bill Francis; Iftekhar Hasan; Lingxiang Li (Bank of Finland, 2014)
We study the impact of firms' abnormal business operations on their future crash risk in stock prices. Computed based on real earnings management (REM) models, firms' deviation in real operations from industry norms (DRO) is shown to be positively associated with their future crash risk. This association is incremental to that between discretionary accruals (DA) and crash risk found by prior studies. Moreover, after Sarbanes-Oxley Act (SOX) of 2002, DRO's predictive power for crash risk strengthens substantially, while DA's predictive power essentially dissipates. These results are consistent with the prior finding that managers shift from accrual earnings management (AEM) to REM after SOX. We further develop a suspect-firm approach to capture firms' use of DRO for REM purposes. This analysis shows that REM-firms experience a significant increase in crash risk in the following year. These findings suggest that the impact of DRO on crash risk is at least partially through REM.
URN:NBN:fi:bof-201410243022
Keywords: 330